The Curriculum Of Love In The Perspective Of The Qur'an And Psychology: New Trends In Holistic Islamic Education - Sidik, Anwar; Sari, Rizka (Halaqa: Journal of Islamic Education, 2025)
This study is important as it responds to the growing need for education that emphasizes not only cognitive development but also students’ emotional well-being. The primary objectives of this research are: (1) to analyze the concept of love from the perspectives of the Qur’an and psychology, (2) to examine the role of the Curriculum of Love in the context of holistic Islamic education, and (3) to explore the implementation of this curriculum in contemporary Islamic educational institutions. The research employs a library study method with a descriptive-analytical approach, involving the analysis of Qur’anic commentaries, educational psychology literature, and relevant studies on Islamic curriculum development. The findings reveal that the concept of love in both the Qur’an and psychology is closely related to character formation, a sense of security, and learning motivation. The Curriculum of Love has been shown to improve the quality of relationships within schools and foster a supportive learning environment. The novelty of this study lies in the integration of transcendental values with psychological and scientific approaches to curriculum design, implying the need for educational policies that prioritize compassion-based learning in Islamic education.